2022
DOI: 10.3389/fpls.2022.1017043
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PGP traits of Bacillus cereus NDRMN001 and its influence on Cajanus cajan (L.) Millsp. phytoremediation potential on metal-polluted soil under controlled conditions

Abstract: The current study looked at the plant growth-promoting (PGP) traits of the pre-isolated and metal-tolerant Bacillus cereus NDRMN001 as well as their stimulatory effect on the physiology, biomolecule content, and phytoremediation potential of Cajanus cajan (L.) Millsp. on metal-polluted soil. The bauxite mine, which is surrounded by farmland (1 km away), has been severely polluted by metals such as Cd (31.24 ± 1.68), Zn (769.57 ± 3.46), Pb (326.85 ± 3.43), Mn (2519.6 ± 5.71), and Cr (302.34 ± 1.62 mg kg−1) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…As in previous studies [ 6 , 35 , 39 ], Actinobacteriota and Proteobacteria were the most abundant rhizospheric phyla in all seasons. A high abundance of Bacillus , a genus rich in PGPB [ 40 ], was observed at lower taxonomic levels. Similarly, Ikeda et al [ 6 ] observed a high abundance of Bacillus , but only in the early growth stages (May and/or July).…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies [ 6 , 35 , 39 ], Actinobacteriota and Proteobacteria were the most abundant rhizospheric phyla in all seasons. A high abundance of Bacillus , a genus rich in PGPB [ 40 ], was observed at lower taxonomic levels. Similarly, Ikeda et al [ 6 ] observed a high abundance of Bacillus , but only in the early growth stages (May and/or July).…”
Section: Discussionmentioning
confidence: 99%